Keabsahan Surat Penetapan Tersangka Dan Surat Penghentian Penyidikan Dalam Perspektif Hak Asasi Manusia - Nurman, Nurman; Thalib, Hambali; Razak, Askari (Journal of Lex Theory (JLT), 2024)
Tujuan penelitian menganalisis keabsahan surat penetapan tersangka dan surat penghentian penyidikan dalam perspektif hak asasi manusia. 2). Untuk mengetahui dan menganalisis faktor yang menyebabkan keabsahan surat penetapan tersangka dan surat penghentian penyidikan dalam perspektif hak asasi manusia. Tipe penelitian ini adalah yuridis empiris. Hasil Penelitian penulis mendapatkan bahwa: 1). Bagaimanakah keabsahan surat penetapan tersangka dan surat penghentian penyidikan dalam perspektif hak asasi manusia apakah sudah berjalan secara optimal. 2). Faktor apakah yang menyebabkan keabsahan surat penetapan tersangka dan surat penghentian penyidikan dalam perspektif hak asasi manusia di wilayah hukum Kepolisian Resor Selayar yaitu; substansi, struktur, dan budaya hukum. Pada ketiga faktor tersebut yang paling berpengaruh terhadap keabsahan surat penetapan tersangka dan surat penghentian penyidikan. The research objective is to analyze the validity of the suspect's determination letter and the letter of termination of investigation from a human rights perspective. 2). To find out and analyze the factors that cause the validity of the suspect's determination letter and the letter of termination of investigation from a human rights perspective. This type of research is empirical juridical. The author's research results found that: 1). How is the validity of the letter to determine the suspect and the letter to stop the investigation from a human rights perspective? Is it running optimally? 2). What factors cause the validity of the suspect determination letter and the letter to stop the investigation from a human rights perspective in the jurisdiction of the Selayar Resort Police, namely; substance, structure and legal culture. These three factors have the greatest influence on the validity of the suspect determination letter and the investigation termination letter.